Evaluation of Dysphagia and Inhalation Risk in Neurologically Impaired Children Using Esophageal High-Resolution Manometry with Swallowing Analysis - Anna Maria Caruso; Denisia Bommarito; Vincenza Girgenti; Glenda Amato; Adele Figuccia; Alessandra Casuccio; Annalisa Ferlisi; Rosaria Genuardi; Sabrina La Fata; Rosalia Mattei; Mario Pietro Marcello Milazzo; Maria Rita Di Pace (MDPI AG, 2022)
Background: Dysphagia in neurologically impaired children is associated with feeding difficulties, malnutrition and aspiration pneumonia. Esophageal high-resolution manometry (HRM) has been used in the diagnosis of motility disorders affecting the swallowing process. The aim of this study was to analyze swallowing functions in NI children by using HRM in order to establish swallow parameters identifying inhalation risk. Methods: Twenty-five NI children with cerebral palsy were submitted to esophageal HRM with UES analysis, comparing the results with non-NI children. The following parameters were evaluated: maximum pressure and duration of contraction of the velopharynx (VP) and tongue base (TB), and maximal, minimal, resting pressure and relaxation duration of the upper esophageal sphincter (UES). Results: pVP max, pTB max, pUES max and resting pressure were lower, while p UES minimal was higher and relaxation duration was shorter in NI children vs. the control group. Predictive values of inhalation risk were evaluated. Conclusions: This study evaluates inhalation risk in NI children using HRM to study UES function. Our results confirm the alterations described in NI children: insufficient contraction and clearing force for bolus transmission through the pharynx and incomplete UES relaxation can predispose to pharyngeal residues and inhalation independently of swallowing because of lower values of UES resting.